Enacting collaborative writing in an academic writing class - Ika Widhy Retnary (Universitas Sarjanawiyata Tamansiswa, 2021)
Abstract: This research aims to find out how the implementation of collaborative writing techniques improves the International Relations students’ writing skills in an argumentative essay and its efficacy of the collaborative writing performance with Kemmis and Taggart’s action research (CAR). This research involved thirteen International Relations students of Essay Writing class. A writing task was given as a pre-test and task to find out the problem faced by the students and to identify the changes they had after implementing the technique. A questionnaire was distributed at the end of cycle 2 to identify the efficacy of the implementation and the changes in the students’ attitudes. The findings showed that the collaborative writing technique gave the students chance to improve their writing skills in argumentative essays. This was seen from the significant change in the final stage that raised to 16.23%. The implementation of the collaborative writing technique allowed students to be motivated, responsible, and confident more in the smooth and enjoyable learning processes. Keywords: argumentative essay, CAR, writing skill.